2007 IEEE International Conference on Industrial Engineering and Engineering Management 2007
DOI: 10.1109/ieem.2007.4419289
|View full text |Cite
|
Sign up to set email alerts
|

A competitive framework for the South African clothing industry

Abstract: The SA clothing industry has shed over 67 000 jobs in the past three years [1]. There is a possibility that more jobs may be shed in the South African clothing industry over the next few years [1]. The SA clothing industry is facing a great challenge because of the rapidly changing business environment with respect to global competition, market performance, and advancing technology. The study is part of doctoral thesis and has focused on the development of a framework that would assist to reaffirm and re-estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Some improvements have been shown to be possible in 2 case studies in the South African clothing industry by using elements of a developed framework judiciously [12] [13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some improvements have been shown to be possible in 2 case studies in the South African clothing industry by using elements of a developed framework judiciously [12] [13].…”
Section: Discussionmentioning
confidence: 99%
“…It is thus suggested that with the application of elements of the framework of process improvement introduced previously [12][13] by the authors, the clothing industry could improve labour efficiency substantially in the South African clothing industry context. Management needs to take the initiative of getting in the required skills to implement these changes, which could almost double their current profitability [13].…”
Section: Organisation Bmentioning
confidence: 99%
See 2 more Smart Citations